PENERAPAN METODE PEMBELAJARAN AKTIF COURSE REVIEW HORAY TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 18 PADANG - Kurnia, Dewi; Anggraini, Villia; Pratiwi, Merina (Pendidikan Matematika, 2014)
ABSTRACT               This research was based on opinions of the students that mathematical was a difficult, boring lesson. This was supported by the fact that their understanding of mathematical concept was still low. The purpose of the research was to study whether students understanding of  mathematical concept by using Course Review Horay active learning method was better than understanding of mathematical concept by using conventional learning. This was an experimental research which used random toward the subject design. The instrument of the research was an essay posttest whose reliability was 0,83. Based on the result of hypothesis testing, it is found that tcount is 1,85 and ttable is 1,645,  so tcount > ttable  then the hypothesis is accepted. It can be conclude that the students understanding of mathematical concept by using Course Review Horay active learning method was better than understanding of mathematical concept by using conventional learning in class VIII of SMPN 18 Padang.